Strategi Pemberdayaan Masyarakat dalam Meningkatkan Partisipasi dalam Pembangunan Desa Payakameng - Mohd. Andalusia Masri; Mifzal Ibrahim; Marta Hadi (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Community service in village development aims to strengthen community participation in planning, budgeting, and evaluating the results of village development in a more participatory manner. This study used a participatory and qualitative approach with data collection techniques through focus group discussions, interviews, and field observations. This service is focused on training and skills provision for community members in planning, budgeting and evaluating village development programs. The results of the service show that through training and skills provision, community members are able to increase their participation in planning, budgeting and evaluating village development results. In addition, community service also encourages the creation of synergies between the village government and the community in strengthening community participation in more inclusive and sustainable village development. Thus, community service can be one of the solutions to strengthen community participation in more participatory and sustainable village development.